Language Building Nature: Ecolinguistic Framing Analysis on The Environmental Conservation Hashtag @Griya_Luhu - Muliawan, Made Sani Damayanthi; I Wayan Simpen; Made Sri Satyawati; I Nyoman Suparwa (International Journal of Multilingual Education and Applied Linguistics, 2024)
Language is not just a means of communication, but a force that shapes our perspective and behavior towards the environment. In the digital era, social media has become an important platform for environmental conservation campaigns, with hashtags (#hashtag) functioning as frames that direct meaning and mobilize action. This research examines how the Instagram account @griya_Luhu uses hashtags to campaign for environmental issues. Through ecolinguistic framing analysis of popular hashtags used, this research reveals @griya_Luhu's strategy in: Framing environmental problems and solutions, defining individual and collective roles, and promoting pro-environmental values. The research results show that @griya_luhu effectively simplifies complex issues, encourages real action, and builds collective awareness. However, some potential biases and simplifications need to be criticized. This research underscores the importance of language analysis in examining the effectiveness of environmental campaigns on social media and provides an analytical framework for future similar research.conservation. Keywords Enviromental Conservation Hasthag, Framing, Ecolinguistic.